Plastic pollution prevention in Pacific Islands: Gap Analysis of Current Legislation, Policies and Plans - Farrelly T; Borrelle S; Fuller S (EIA, 2020)
Using a gap analysis, this study aims to identify the current limitations in national plastic pollution policy for preventing plastic pollution. It also explores the potential to implement best practice for the reduction of plastic pollution and the promotion of a safe circular plastics economy.